Experimental prediction of wear rate on rail and wheel materials at dry sliding contact - Windarta, (EDP Sciences, 2014)
This research is aimed at predicting the rail gauge and wheel flange contacts and their influences to wear rate using pin-on-disc method. A real model using a pin to represent a wheel component and a disc to represent a rail component were fabricated for the experiments. The experimental results were analyzed and the empirical formula of the wear depths as functions of applied load, bulk temperature and sliding velocity were obtained to describe the behavior of the systems. The results showed that the wear depth increased linearly with the increasing in applied load and temperature, while it decayed exponentially with the sliding velocity. The results were found to agree with the twin disc models from previous research works. Â© 2014 Owned by the authors, published by EDP Sciences.